MUCOPOLYSACCHARIDOSES: PSYCHOSOCIAL VULNERABILITY OF FAMILY CAREGIVER - Castañeda-Ibáñez, Nolly Nataly; Campos-Sánchez, Marcela (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2020)
Background: The majority of caregivers are family members and within the symptoms that the caregiver may present, there are manifestations of stress, psychological state of overload, stress or discomfort caused by the continuous provision of care for the family member, feelings and negative perceptions regarding their caring function.Objective: The purpose of this research is to study the psychosocial vulnerability of family caregivers of patients with Mucopolysaccharidoses (MPS).Methods: This study is based on a mixed method with a cross sectional and a descriptive approach. The first stage was quantitative and the second stage was qualitative, both of them to explore the psychosocial vulnerability of a group of family caregivers of patients (n=111) with MPS belonging to the Colombian association of patients with lysosomal storage diseases ACOPEL by its acronym in Spanish. This study collects quantitative data using the patient admission request format from ACOPEL, employed to obtain relevant sociodemographic variables: Gender, Age, Marital status, Education, Occupation, living area, type of housing, live with, socioeconomic stratum, monthly income and time spent as a caregiver. And this study collects qualitative data using a structured interview held to psychologists and healthcare professionals belonging to ACOPEL.Results: The results show that most of them are women, relatives in a relationship or married; most of them belonging to a low socioeconomic stratum and a low professional education. The categories of analysis revealed were the attitude is towards illness, taking account diagnosis and health staff, support networks and psychoeducation. Secondly, the impact of care work on the physical and psychological health of female caregivers. Third, coping resources and finally the double mother role-caregiver and her emotional bond with the patient.Conclusion: In conclusion, the attitude and knowledge towards the disease depend on the diagnosis and the prognosis according to the type of MPS. It is important more research the psychosocial aspects and vulnerability of family caregivers in patients with MPS to develop evidence-based knowledge, psychoeducation, and, appropriate interventions.